Methods for Imaging Inflammation and Transendothelial Migration in Vivo and ex Vivo. Issue 4 (20th April 2023) - Fang, Vivienne; Haynes, Maureen E.; Hayashi, Vanessa; Arias, Erika; Lavine, Jeremy A.; Sullivan, David P.; Muller, William A.
Abstract: Inflammation is the body's response to injury and harmful stimuli and contributes to a range of infectious and noninfectious diseases. Inflammation occurs through a series of well‐defined leukocyte‐endothelial cell interactions, including rolling, activation, adhesion, transmigration, and subsequent migration through the extracellular matrix. Being able to visualize the stages of inflammation is important for a better understanding of its role in diseases processes. Detailed in this article are protocols for imaging immune cell infiltration and transendothelial migration in vascular tissue beds, including those in the mouse ear, cremaster muscle, brain, lung, and retina. Also described are protocols for inducing inflammation and quantifying leukocytes with FIJI imaging software. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Induction of croton oil dermatitis Alternate Protocol 1 : Induction of croton oil dermatitis using genetically fluorescent mice Basic Protocol 2 : Intravital microscopy of the mouse cremaster muscle Support Protocol : Making a silicone stage Basic Protocol 3 : Wide‐field microscopy of the mouse brain Basic Protocol 4 : Imaging the lungs (ex vivo) Alternate Protocol 2 : Inflating the lungs without tracheostomy Basic Protocol 5 : Inducing, imaging, and quantifying infiltration of leukocytes in mouse retina